Bismuth-Based Quadruple Therapy with Bismuth Subcitrate, Metronidazole, Tetracycline and Omeprazole in the Eradication of Helicobacter pylori. (1st September 2001) - Lahaie, Raymond; Farley, Alain; Dallaire, Chrystian; Archambault, André; Fallone, Carlo A; Ponich, Terry; Hunt, Richard; Oravec, Michael; Whitsitt, Paul; Van Zanten, Sander Veldhuyzen; Marcon, Norman; Bailey, Robert; et al.
Abstract : BACKGROUND: A previous study showed that 14 days of qid bismuth-based triple therapy with tetracycline 500 mg, metronidazole 250 mg and colloidal bismuth subcitrate 120 mg resulted in excellent Helicobacter pylori eradication rates (89.5%). The present study looked at a shorter treatment period by adding omeprazole and by reducing the dose of tetracycline. METHODS: One hundred sixty-one patients with H pylori confirmed by histology and 13 carbon urea breath test were included in the study. They were treated for seven days with bismuth subcitrate 120 mg plus metronidazole 250 mg plus tetracycline 250 mg qid plus omeprazole 20 mg bid (OBMT). Patients were 18 to 75 years of age and had dyspepsia with or without a history of peptic ulcer. Patients with irritable bowel syndrome, active ulcer or previous attempt at eradication, or those who had used antibiotics or antiulcer drugs in the previous 30 days were excluded. Eradication was determined by two 13 carbon urea breath tests done one and three months, respectively, after treatment. Strains with minimal inhibitory concentrations of 8 µg/mL or higher were considered to be resistant to metronidazole. RESULTS: The overall per protocol eradication rate was 84% - 89.5% in metronidazole-sensitive and 70.8% in metronidazole-resistant strains. Modified intent-to-treat analysis resulted in a 80% eradication rate - 82.5% in metronidazole-sensitive and 66.7% in metronidazole-resistant strains. Only one patient discontinued treatment because of adverse events. CONCLUSIONS: The OBMT regimen used in this study is safe and effective against metronidazole-sensitive H pylori strains.